Anticoagulant and antiplatelet use in seniors with chronic subdural hematoma: Systematic review. (16th May 2017) - Nathan, Santhosh; Goodarzi, Zahra; Jette, Nathalie; Gallagher, Clare; Holroyd-Leduc, Jayna
Abstract : Objective: To address whether to restart older patients on anticoagulants or antiplatelet agents in the setting of a chronic subdural hematoma (cSDH). Methods: This is an update of a previous review (searched until July 2012). Medline, EMBASE, ISI Web of Knowledge, Google Scholar, PLOS, and the Cochrane Register for Systematic Reviews databases were searched from January 2012 to December 2016. Studies included older adults (those over 65 years) experiencing traumatic subdural hematoma or cSDH who were on anticoagulation or antiplatelet agents. Results: Seven studies were included (mean age 72 years). Four out of 7 studies provided combined data on anticoagulants or antiplatelet use. Only one study found anticoagulant or antiplatelet agent use to be a significant factor for cSDH rebleeding. Two studies considered anticoagulant use only and both reported similar increased odds of rebleeding (odds ratio [OR] 1.75, 95% confidence interval [CI] 0.18–16.86; OR 2.7 95% CI 1.42–6.96). Antiplatelets were not found to be associated with rebleeding. Ideal timing to resume anticoagulants or antiplatelets was unclear. Conclusions: Anticoagulant medication was associated with increased rebleeding risk in older adults with cSDH. However, antiplatelet medication was not associated with increased risk of rebleeding.